Exposure of Fluoride with Streptozotocin-Induced Diabetes Aggravates Testicular Damage and Spermatozoa Parameters in Mice - Manuel Sánchez-Gutiérrez; Evelia Martínez-Loredo; Eduardo Osiris Madrigal-Santillán; Gabriel Betanzos-Cabrera; Araceli Hernández-Zavala; María Angélica Mojica-Villegas; Jeannett Alejandra Izquierdo-Vega (Journal of Toxicology)
Diabetes mellitus is the most common chronic disease worldwide that causes numerous complications, including male infertility. The prevalence of DM is 451 million people and estimated that would increase to 693 million in 2045. Fluorosis caused by drinking water contaminated with inorganic fluoride is a public health problem in many areas around the world. Previous studies have shown that fluoride exposure damages the male reproductive function. This study aimed to evaluate the fluoride sub-chronic exposure on the spermatozoa function in streptozotocin (STZ)-induced diabetic mice. After confirming diabetes by measuring blood glucose levels, the male mice received 45.2 ppm of fluoride added or deionized water. We evaluated several parameters in diabetic mice exposed to fluoride: standard quality analysis, the mitochondrial transmembrane potential (ψm), the caspase activity in spermatozoa, urinary fluoride excretion, and histological evaluation in the testes. After 60 days of fluoride-exposure, diabetic mice, significantly decreased sperm quality (motility, viability, and concentration). Spermatozoa from fluoride-exposure in diabetic mice presented a significant decrease in ψm and a significant increase in activity caspase 3/7. Urinary fluoride excretion was decreased in diabetic mice exposed to fluoride. Subchronic fluoride exposure of mice with STZ-induced diabetes aggravated testicular damage and the spermatozoa function.